Scary Acute Left Main Coronary Artery Thrombus as an Initial Presentation of a Hereditary Thrombophilia: When to Go Out of Routine? - Kilic, Sinem; Ates, Ahmet Hakan; Canpolat, Uğur; Aytemir, Kudret (European Journal of Therapeutics, 2023)
Patients with either hereditary or acquired thrombophilia can present with arterial and venous thrombotic complications. However, it is unclear to whom the thrombophilia panel should be assessed, particularly in patients presenting with a common cardiovascular risk factor and acute coronary thrombus. Herein, we presented the management of an active smoker female patient who presented to our emergency room with inferior acute ST-segment elevation myocardial infarction, and hereditary thrombophilia has been diagnosed due to the presence of substantial left main coronary artery thrombus.